Legal Perspective on the Practice of Illegal Mobile Phone Trading with Fake IMEI - Arifin, Syasyain; Maswandi, Maswandi; Rafiqi, Rafiqi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The illegal trade of mobile phones with fake IMEI is a serious problem that has an impact on various aspects, including economic, legal, as well as security and social. This study aims to analyze the legal arrangements, impacts, and legal liabilities for those who sell mobile phones with illegal IMEI in Indonesia. The method used in this study is a qualitative approach with normative analysis techniques on laws and regulations, case studies, and studies of previous research. The results of the study show that although regulations related to IMEI control have been implemented through the Telecommunications Law, the ITE Law, and the Regulation of the Minister of Communication and Information, their implementation and supervision are still experiencing obstacles. From an economic perspective, the circulation of illegal devices causes state losses due to the loss of potential taxes and import duties. From a legal perspective, weak supervision of marketplaces and distribution networks of illegal devices hinders the effectiveness of the policies that have been set. In addition, sanctions against illegal IMEI traders still do not provide an optimal deterrent effect. This study recommends strengthening law enforcement, increasing supervision of online marketplaces, and educating the public about the importance of buying devices with official IMEIs. With these steps, it is hoped that the circulation of illegal mobile phones can be suppressed and IMEI regulations can run more effectively.